8. IMPLEMENTASI INTERNATIONAL SHIP AND PORT FACILITY SECURITY (ISPS) CODE DALAM MENCEGAH PETTY THEFT DAN ARMED ROBBERY AGAINST SHIPS DI INDONESIA TAHUN 2009-2013 - Rindarto, Aska Putratama; Windiani, Reni; P, Shary Charlotte (Journal of International Relations, 2016)
Shipping has been the most reliable system and important in the interstate commerce forits ease and efficiency. But it will not come without any risk, numerous maritime crimethat threaten the vessels and ports such as petty theft and armed robbery against shipsmade the international community agreed to implement the International Ship and PortFacility Security ( ISPS ) Code for the urge of security of shipping activity in their ownterritory. Indonesia as one of the country that implementing the ISPS Code have failed tolower the crime rate in its area from 2009 to 2013. As for the failure was caused by the lessmaximum coverage of the ISPS Code as an international rules and human resources factorbeside the insufficient facilities in the ports of Indonesia, all of which were analyzed usingthe concept of Order of Hedley Bull.